Handbook of Florida Water Regulation: Northern Everglades and Estuaries Protection Program - Michael T. Olexa; Zachary Broome (EDIS, 2011)
Lost in the maze of statutes, regulations, and potential liabilities that identify the current mass of water protection law? This revised document is part of the Handbook of Florida Water Regulation, which consists of 2-4 page fact sheets that provide an accurate, current, and authoritative summary of the principal, federal, and state (Florida) laws that directly or indirectly relate to agriculture. It provides a basic overview of the many rights and responsibilities that farmers and farmland owners have under both federal and state laws as well as the appropriate contact information to obtain more detailed information. Written by Michael T. Olexa and Zachary Broome, with contributions by Tatiana Borisova, and published by the UF Department of Food and Resource Economics, June 2011.